Recent Publications upon Economics (Quarterly Journal of Economics, 1887)
Recent Publications upon Economics The Quarterly Journal of Economics, Volume 1, Issue 3, April 1887, Pages 378–384, https://doi.org/10.1093/qje/1.3.378 Published: 01 April 1887